Pre‐diabetes and well‐controlled diabetes are not associated with periodontal disease: the SHIP Trend Study. (27th April 2015) - Kowall, Bernd; Holtfreter, Birte; Völzke, Henry; Schipf, Sabine; Mundt, Torsten; Rathmann, Wolfgang; Kocher, Thomas
Abstract Aim To examine associations of pre‐diabetes and well‐controlled diabetes with periodontitis. Materials and Methods The Study of Health in Pomerania (SHIP)‐Trend is a cross‐sectional survey in North‐Eastern Germany including 3086 participants (49.4% men; age 20–82 years). Clinical attachment loss (CAL) and periodontal probing depth (PPD) were assessed applying a random half‐mouth protocol. The number of teeth was determined. Pre‐diabetes comprised impaired fasting glucose and impaired glucose tolerance. Previously known diabetes was defined as well controlled if glycated haemoglobin (HbA1c) was <7.0%. Participants were categorized as follows: normal glucose tolerance (NGT), pre‐diabetes, newly detected type 2 diabetes (T2DM), known T2DM with HbA1c<7.0% and known T2DM with HbA1c≥7.0%. Results Pre‐diabetes was neither associated with mean CAL and PPD in multivariable adjusted linear regression models nor with edentulism (OR = 1.09 (95%‐CI: 0.69‐1.71)) and number of teeth (OR = 0.96 (95%‐CI: 0.75–1.22), lowest quartile versus higher quartiles) in logistic regression models. Associations with mean CAL and edentulism were stronger in poorly controlled previously known diabetes than in well‐controlled previously known diabetes (for edentulism: OR = 2.19 (95%‐CI: 1.18–4.05), and OR = 1.40 (95%‐CI: 0.82–2.38), respectively, for comparison with NGT). Conclusions Periodontitis and edentulism were associated with poorly controlled T2DM, but not with pre‐diabetes and well‐controlled diabetes.